Economic profitability of oyster mushroom production in Botswana - Khare, K B; Khonga, E B; Jongman, M; Leteane, M (Mushroom Research, 2016)
A hybrid of Pleurotus ostreatus x Pleurotus florida (Po x Pf), was cultivated in a low technological mushroom house at the Botswana College of Agriculture, Sebele. This oyster mushroom was grown on maize cobs, two grass species (Cenchrus ciliaris and Eragrostis pallens) and water reed (Phragmetes sp.) supplemented with 20% each of wheat bran, gram flour and cowpea pods. The highest yield of the mushroom (84.9 BE%) was obtained from pasture grass (C. ciliaris) supplemented with cowpea pods whereas BE % 82.50 was obtained when this substrate was supplemented with wheat bran and gram flour. The wheat bran, gram flour and cowpea pods when supplemented to the substrates increased the final yield of the mushroom by 8% to 20%.Maize cobs, Eragrostis pallens and Phragmetes sp. performed poorly even when supplemented, in terms of incubation period, days from spawning to the fruiting up to third flush and yield of the mushroom. Three yields, experimental yield, expected yield (80% of experimental yield) and pessimistic yield (60% of experimental yield) were used in calculation of cost-profit analysis. The experimental yield was obtained on 500 Kg of dried pasture grass as a substrate. The maximum profit of 208% (an income of BWP7458.00 per month) was observed when experimental yield was considered, and a profit of 146% (BWP 5248.00/month) and 85% (BWP 3038.00/month) can be achieved even when 80% and 60% of the experimental yield were taken into account, respectively. The profit analysis showed that oyster mushroom cultivation is a potential income generating enterprise which can be adopted by small-scale farmers and unemployed youth in Botswana.